Developing the 'Save the Earth!' E-Module as an ESD-Based Learning Tool to Enhance Sustainability Awareness and Critical Thinking among Indonesian Students (Universitas Pendidikan Indonesia, 2026)
This study aims to develop and evaluate the Save the Earth! e-module based on Education for Sustainable Development (ESD) to enhance students' critical thinking and sustainability awareness within the framework of the Pancasila Student Profile Project (P5). Utilizing the ADDIE development model, the e-module was designed around five interactive learning stages (Orientation, Contextualization, Real Action, Mini Exhibition, and Final Reflection) and integrated multimedia features to support project-based learning. The module's feasibility was assessed by expert validators, yielding average scores of 4.50 (media expert) and 4.60 (content expert), both categorized as